A STRUGGLE: THE EXPERIENCES AND NEEDS OF FIRST-YEAR SANTRI AT PESANTREN - Sa’diah, Halimatus; Kamila, Aisyatin; Muarif, Ahmad Syamsul; Lidyawangi, Cemara Syifa (Jurnal At-Taujih, 2024)
The adaptation process is always experienced by new santri. However, some santri have difficulty getting through their first year due to differences in activities from their previous home habits. The focus of this study is to see the description of the experiences and needs of new santri in the first year. Participants are santri who have passed their first year at the Islamic boarding school with a total of 54 santri. Data collection was carried out through face-to-face interviews and Focus Group Discussions (FGD). As a result, there are two main themes in this study. First, related to the experiences of new santri, three most common things experienced by new santri were found, namely: (1) culture shock), (2) homesickness, and (3) social problems of friendship. Second, the results related to the needs of new santri in the first year of adaptation to the Islamic boarding school environment, participants require: (1) attention, (2) guidance by seniors, (3) justice from the Islamic boarding school administrators.